Batgirl. Vol. 1, Mother - Brombal, Tate (DC Comics, 2025)
"Cassandra Cain, one of the most popular characters to wear the Batgirl cowl, is back in the spotlight--and ready for the deadliest mother/daughter team-up in comic book history! Hold on to your seats, clutch your pearls, and rejoice in celebration because Cassandra Cain is taking center stage in her first solo Batgirl series in nearly two decades--as part of DC's bestselling All In new-reader-friendly story initiative! When a deadly group of assassins shows up to kill Cassandra, her mother Lady Shiva--the deadliest assassin in the DC Universe--comes to the rescue, and they must put their complicated past aside and work together as mother and daughter to ensure they make it out alive. Unfortunately, things are never as easy as they seem, and Cass must embark on a jaw-dropping, martial-arts-filled adventure in her quest for truth and justice...and revenge?! It's a Batgirl story like never before, as writer Tate Brombal and artist Takeshi Miyazawa dive into the psyche of one of Gotham's deadliest fighters while exploring her deep and complex relationship with her mother."-- Publisher.